(untitled) (Itinera, 2023)
Beginning with the work of Olafur Eliasson, with particular reference to the recent exhibition “Trembling Horizons” but not limited to it, a number of works representative of an artistic vision that might be called eco-logical are analyzed. Not only by explicitly thematizing the issue of the environmental crisis, Eliasson’s works seem to materially express the demands of theorists who question how art can actively respond to the need for a shift in outlook that characterizes current events. Starting from the idea of art as praxis, which allows the viewer to regard himself or herself and to place himself or herself in relation to what surrounds us – human and non-human – Eliasson’s works act on the intrinsic objecthood of the work itself by creating a relationship with otherness and datity. They generate, therefore, a feeling of proximity, which concretizes a meaning of creativity in a transformative and site-specific sense; they promote an eco-logic that has its basis in a nomadic and depotentiated vision of subjectivity, engendering a feeling of interconnectedness and care. It will be argued in this paper the need to rethink art in these terms by hypothesizing a particular efficacy of some works that actively work in public space: places where the split between nature and culture has taken place, urban and public space are privileged contexts to actively promote the overcoming of this fracture and generate ethically responsible, already intrinsically ecological subjects.